Language, Identity, and Inclusion: Advancing Multilingual Education Through Culturally Responsive Pedagogy in Indonesia - Marwah, Sopa Siti; Anisah, Ani Siti; Nurzakiah (Eduscape : Journal of Education Insight, 2025)
This study explores the implementation of Culturally Responsive Pedagogy (CRP) in multilingual Indonesian classrooms within the framework of national curriculum reforms. Indonesia’s linguistic diversity spanning over 700 local languages poses both challenges and opportunities for inclusive education. This research investigates how policies such as Kurikulum Merdeka and Profil Pelajar Pancasila are translated into practice across three regions: Papua, Sulawesi, and Yogyakarta. Using a qualitative case study approach, the study gathered data through semi-structured interviews, classroom observations, and document analysis. Participants included 18 educators and administrators. Data were analyzed thematically using NVivo, focusing on four key dimensions: policy-practice gaps, teacher capacity, resource constraints, and community engagement. Findings indicate that despite national support for cultural inclusion, implementation of CRP is constrained by limited teacher training, the dominance of standardized assessments, and a lack of culturally relevant teaching materials. Language prestige also influences pedagogical decisions, often sidelining local languages in favor of Bahasa Indonesia and English. However, schools that actively engaged local communities and integrated indigenous knowledge into learning reported improved student engagement and cultural affirmation. The study concludes that realizing the full potential of CRP in Indonesia requires systemic reforms that empower teachers, decentralize curriculum design, and institutionalize community partnerships. These changes must be supported by targeted policies and sustained investment in multilingual and multicultural education.